Creation the Overlapping Ordinary Sets by Complementary Approach - Kadum Abbas Zeyarah, Abdulrahman; ., . (International Journal of Engineering and Technology, 2018)
The present paper reports definition of overlapping ordinary sets and represent how to nest only one set, comparable sets, and disjoint sets by using basic concepts of the set theory, in especially absolute complement operations.Â Â Â It found that the most useful entrance to develop a definition of overlapping ordinary sets is reasonable definition of incomparable sets.Â Â Overlap relation, Overlap operation and Overlap function was studied in a manner featured.Â Â Â It is shown that the double complement with different types of complement operations (Absolute, Relative), are not necessary equal to the same results.Â In addition to the paper studied separable overlapping ordinary sets.Â Â